Immediate loading of short implants: A systematic review - Mahdi Hadilou; Pooya Ebrahimi; Behnaz Karimzadeh; Ashkan Ghaffary; Leila Gholami; Zahra Fathifar (Tabriz University of Medical Sciences, 2021)
Background. This systematic review aimed to determine the effectiveness and outcomes of immediate loading methods for short dental implants. Methods. The authors independently conducted an electronic search in the PubMed, Embase, EBSCO, ProQuest, and Cochrane databases for relevant articles published until November 15, 2020. The references of the included studies were assessed, and a manual search was conducted in Google Scholar and PubMed to find additional relevant studies. Results. Finally, three studies were selected and included in this systematic review. Significant heterogeneity existed in the design of the included studies, and due to the low number of the included studies, the authors could not perform a meta-analysis. The studies showed that the survival rate of immediate-loaded short implants is comparable to conventional loading methods. However, more marginal bone loss is expected. Overall, the immediate loading of short dental implants might be clinically successful. Conclusion. Based on the results, immediate loading protocols might be safely used for short implants. However, caution should be exercised in interpreting these results. Future welldesigned randomized clinical trials with more participants and study power are necessary to support the findings of this systematic review.